David : the nation's most respected gay weekly publication. (Fort Lauderdale : The David Weekly Magazine, 1999)
Fonds Suzan Daniel (FSD)
Periodiciteit: wekelijks
Redactie: 2500 Wilton Drive, Fort Lauderdale, FL 33305
Engels
Periodiek